2022
DOI: 10.1371/journal.pone.0265500
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of machine learning-driven prediction model for serious bacterial infection among febrile children in emergency departments

Abstract: Serious bacterial infection (SBI) in children, such as bacterial meningitis or sepsis, is an important condition that can lead to fatal outcomes. Therefore, since it is very important to accurately diagnose SBI, SBI prediction tools such as ‘Refined Lab-score’ or ‘clinical prediction rule’ have been developed and used. However, these tools can predict SBI only when there are values of all factors used in the tool, and if even one of them is missing, the tools become useless. Therefore, the purpose of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A previous supervised learning model for risk stratification of febrile infants acknowledged that it lacked parameter cutoffs and was computationally complex 11 . While machine learning models have promising performance compared to traditional scoring systems 12 , 18 , these have been difficult to translate to clinical practice because of the lack of recommended thresholds for action. In contrast, we assigned risk scores that quantified risk for SBI at each predictive risk threshold.…”
Section: Discussionmentioning
confidence: 99%
“…A previous supervised learning model for risk stratification of febrile infants acknowledged that it lacked parameter cutoffs and was computationally complex 11 . While machine learning models have promising performance compared to traditional scoring systems 12 , 18 , these have been difficult to translate to clinical practice because of the lack of recommended thresholds for action. In contrast, we assigned risk scores that quantified risk for SBI at each predictive risk threshold.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Lee et al [ 50 ] demonstrated the feasibility of using machine learning models to predict bacterial or viral infections based on clinical symptoms and laboratory markers, thereby helping clinicians make informed antibiotic prescribing decisions. In addition to hospital-based applications, AI-DSS has the potential to extend antimicrobial stewardship efforts to community-based healthcare providers such as primary care physicians, urgent care clinics, and long-term care facilities [ 51 ].…”
Section: Optimizing Antibiotic Use Through Artificial Intelligence-gu...mentioning
confidence: 99%